High concentration phosphate removal by calcite and its subsequent utilization for tetracycline removal. (October 2020) - Li, Zhenxuan; Guo, Mengxiao; Sun, Xiaowen; Li, Lucheng; Guo, Xiaolan; Huang, Lidong; Xiao, Jiangtian; Xu, Defu; Liu, Dagang
Highlights: Tetracycline could be removed by phosphate-loaded calcite. IR, XPS, XRD and BET analysis suggested occurrence of amorphous phosphate calcium. Precipitated amorphous calcium phosphate promoted tetracycline removal. Tetracycline may be adsorbed on the precipitated amorphous calcium phosphate. Abstract: The excess phosphate and tetracycline (TC) in natural environments potentially threatens ecosystem. Few studies were conducted on efficient and cost-effective method for dealing with these pollutants together. we attempted to reutilize this abandoned calcite for the removal of other pollutant in wastewater, such as tetracycline. Firstly, removal of high concentration phosphate by calcite was studied in batch experiments. Thereafter, removal of TC by this used calcite (P-loaded calcite) was investigated under different conditions: pH, phosphate concentration, dried state and humid state. Using calcite for high concentration phosphate removal, the results showed that (1) concentrations of phosphate higher than 30 mg.L −1, resulted in a significant phosphate precipitation on calcite surface at both pH7.7 and pH 8.3 within 24 h. The corresponding pH and calcium results confirmed this precipitation occurrence; (2) the precipitated phase was supposed to be amorphous calcium phosphate through the results of IR, XPS, XRD and BET analysis. Compared to that by pure calcite, the TC removal rate by P-loaded calcite increased significantly with the initial phosphate concentration in both cases of Humid Experiment and Dried Experiment . This may be attributed to the adsorption of TC on the precipitated amorphous calcium phosphate, which has a larger specific surface and increasingly generates > Ca + sites. From the similarity of TC removal rate by P-loaded calcite between pH7.7 and pH 8.3, it is hypothesized that TC removal is due to TCH2 ° and TCH- adsorption on > Ca + sites. The minor difference of TC removal rate by P-loaded calcites between Humid Experiment and Dried Experiment is mainly due to slight dissolution of precipitated amorphous calcium phosphate. Our research will serve as reference knowledge for the reutilization of abandoned calcite in phosphate removal, which provides a new way to reduce the wasted materials and environmental risks induced by tetracycline.